Women in Business and Management : The Business Case for Change. - Office, International Labour (International Labour Organisation (ILO), 2019)
This report offers new insights into how gender diversity at the top improves organizational performance. These include how the many dimensions of an organization's policies, a gender-balanced workforce and a gender-inclusive culture, among other factors, move the needle for more women to hold decision-making power.
Description based upon print version of record.
Keywords: Women executives.; Organizational effectiveness.; Diversity in the workplace.; Glass ceiling (Employment discrimination); Efficacité organisationnelle.; Multiculturalisme en milieu de travail.; Plafond de verre (Discrimination dans l'emploi); Diversity in the workplace; Organizational effectiveness; Women executives